Overseas qualified nurses' sociocultural adaptation into the Australian healthcare system: A cross-sectional study. Issue 4 (August 2021) - Zanjani, Maya Ebrahimi; Ziaian, Tahereh; Ullrich, Sandra; Fooladi, Ensieh
Abstract: Background: Overseas qualified nurses (OQNs) face various challenges while adjusting to the Australian healthcare system. However, few studies to date have identified specific factors affecting their sociocultural adjustment, health and psychology. Aims: The primary aim was to examine factors associated with OQNs' sociocultural adjustment to the Australian healthcare system. A secondary aim was to determine whether there was a correlation between OQNs' sociocultural adjustment and their mental and physical health. Methods: A questionnaire was sent electronically to 2, 250 randomly selected OQNs through the Australian Health Practitioner Regulation Agency, and later distributed to 50 OQNs in person through Western Health, Melbourne. Sociocultural adjustment was assessed using the Sociocultural Adaptation Scale-Revised. The Nurse International and Transition Questionnaire-2 was used to explore the factors involved in sociocultural adjustment: these were pull factors, push factors, initial experiences, job satisfaction, feeling at home, and reactions to the working environment. The Perceived Stress Scale and General Health Questionnaire-12 were used to assess psychological adjustment and general health, respectively. Findings: A total of 200 participants completed the questionnaire. The mean age (SD) of the participants was 32.79 (6.91) with 161 (80%) holding a bachelor degree. In the adjusted multivariate linear regression, job satisfaction (β = 0.24, 95% CI 0.13 to 0.36), current work environment (β = 0.27, 95% CI 0.05 to 0.49) and feeling at home (β = 0.32, 95% CI 0.13 to 0.50) were independently positively associated with sociocultural adaptation. Sociocultural adaptation was negatively related to PSS (r = −0.14, β = −0.16, p = 0.04) and GHQ12 (r = −0.36, p < 0.001, β = −0.59). Discussion: Three factors (job satisfaction, current work environment, and feeling at home in Australia) were found to be significant in measuring OQNs' level of sociocultural adaptation. When the level of sociocultural adaptation was high, OQNs reported better general and psychological health. Conclusion: Job satisfaction and feeling supported in the workplace are the most important factors influencing OQNs' successful adjustment into the Australian healthcare system.